Opinion Paper: Shopping Centre Longevity Post Covid-19 in Jakarta, Indonesia - Hendyansyah Putra (Journal of Social Research, 2025)
The purpose of the study to state the writer opinion on how important Malls to people after Covid-19 in Jakarta. The writer also wants the reader to initiate sustainability action to be part of their everyday activity in giving prosperity to the community and improve Indonesia’s SDG rank. The study focuses on giving opinion to save Malls in Jakarta for being perish and abandoned as the effect of Covid-19 pandemic. Method that being used in this paper is opinion paper; where the writer trying to demonstrate his opinions on a certain topic, analysing them and draw conclusion from them. The writer using observation as a means to describe the true condition of Malls that looked nearly empty to gain opinion on how these Malls should and can survive post Covid-19 period. The results confirm that these Malls in needs of ideas, renovation, owner support, government support, financial support and stakeholder’s support to survive and contribute to Indonesia’s SDG. More specifically that will lead directly to the prosperity of all stakeholders and Jakarta community.